2021
DOI: 10.3390/biomedicines9070766
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Protein Kinase CK2 in Acute Myeloid Leukemia Cells Using the Clinical-Grade Synthetic-Peptide CIGB-300

Abstract: Protein kinase CK2 has emerged as an attractive therapeutic target in acute myeloid leukemia (AML), an advent that becomes particularly relevant since the treatment of this hematological neoplasia remains challenging. Here we explored for the first time the effect of the clinical-grade peptide-based CK2 inhibitor CIGB-300 on AML cells proliferation and viability. CIGB-300 internalization and subcellular distribution were also studied, and the role of B23/nucleophosmin 1 (NPM1), a major target for the peptide i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…Finally, our in vivo pull-down experiments revealed that CIGB-325 can also interact with CK2 catalytic subunit in MDBK cells, as previously reported in lung cancer and leukemia cells [15,16,38]. CIGB-325 impaired the PI3K/AKT pathway, a CK2-mediated signaling pathway, as evidenced by the phosphorylation of the downstream signaling protein RPS6.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Finally, our in vivo pull-down experiments revealed that CIGB-325 can also interact with CK2 catalytic subunit in MDBK cells, as previously reported in lung cancer and leukemia cells [15,16,38]. CIGB-325 impaired the PI3K/AKT pathway, a CK2-mediated signaling pathway, as evidenced by the phosphorylation of the downstream signaling protein RPS6.…”
Section: Discussionsupporting
confidence: 84%
“…Previous reports from our group have indicated that CIGB-325 also impairs CK2 signaling by direct binding to CK2α catalytic subunit in different cancer cell lines [ 15 , 16 , 38 ]. We finally determined whether this direct peptide–enzyme interaction could also take place within the context of a viral infection induced by BCoV-Mebus in MDBK cells.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, CK2 modulates signaling pathways critical for hematopoietic cell survival and function, and its high expression and activity in acute myeloid leukemia (AML) have been associated with worse prognosis and reduced overall survival ( Kim et al, 2007 ; Quotti Tubi et al, 2017 ). Hence, in the past few years, CK2 has emerged as a promising candidate for molecular-targeted therapy in AML, a disease often characterized by poor long-term outcomes and resistance towards standard chemotherapy ( Buontempo et al, 2018 ; Rosales et al, 2021a ; Klink et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…CIGB-300 is a peptidic inhibitor originally conceived to block the protein kinase CK2 activity through binding to the conserved acidic phosphoacceptor domain of substrates ( Perea et al, 2004 ). The peptide is able to impair proliferation and viability of a variety of human cancer cells, including AML cells lines and primary cells from AML patients ( Perea et al, 2008 ; Rosales et al, 2021a ). However, pull-down assays and phosphoproteomic analysis have suggested that CIGB-300 is able to directly interact with the CK2α catalytic subunit and modulate the CK2-dependant phosphoproteome ( Perera et al, 2020a ; Perera et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…The backbone of therapy remains a combination of cytarabine-and anthracycline-based regimens with allogeneic stem cell transplantation for eligible candidates, but elderly patients are often unable to tolerate such regimens and carry a particularly poor prognosis [24]. Protein kinase CK2 has been found to play pivotal roles in AML biology, and targeting CK2 has emerged as viable therapeutic option [25].…”
Section: Acute Myeloid Leukaemiamentioning
confidence: 99%